6
$\begingroup$

Help with a integral calculus please!?

The equation is

$$\int\ln(x)\cos(1+(\ln(x))^2)\,dx$$

My teacher told me, i have to use substitution? but i can't still solve it.

I've been solving this last week but still i can't get the answer, please help me guys. Thanks!

$\endgroup$
4
  • $\begingroup$ Please check that my edit is correct. $\endgroup$ Mar 14 '16 at 10:38
  • 1
    $\begingroup$ First did you try integration by parts or just type the steps with proper format so that someone might help $\endgroup$ Mar 14 '16 at 10:39
  • $\begingroup$ Hint substitute $1+(ln(x))^2=u$ and then youll get $I=\int e^{(u-1)/2}.cosudu$ where cos can be written as $R(re^{iu})$ $\endgroup$ Mar 14 '16 at 10:50
  • $\begingroup$ @ArchisWelankar, this can't be right. There should be a square root inside the exponential $\endgroup$
    – Yuriy S
    Aug 18 '16 at 14:34
2
$\begingroup$

First, consider the following integral:

$$I(t)=\int\sin(1+(t+\ln(x))^2)\ dx$$

By letting $x=e^u$ and $\sin(\theta)=\Im(e^{i\theta})$, we get

$$I(t)=\int e^u\sin(1+(t+u)^2)\ du=\Im\int e^{u+(1+(t+u)^2)i}\ du$$

This may then be solving using the error function,

$$\int e^{u+(1+(t+u)^2)i}\ du=\frac{-\sqrt{\pi i}e^{i+\frac{(2it+1)^2}{4i}}\operatorname{erf}\left(\frac{2iu+2it+1}2\sqrt i\right)}2$$

It then follows that

$$I'(t)=\frac d{dt}\int\sin(1+(t+\ln(x))^2)\ dx=\int2(t+\ln(x))\cos(1+(t+\ln(x))^2)\ dx\\I'(t)=\Im\frac d{dt}\frac{-\sqrt{\pi i}e^{i+\frac{(2it+1)^2}{4i}}\operatorname{erf}\left(\frac{2iu+2it+1}2\sqrt i\right)}2$$

Thus,

$$\frac12I'(0)=\int\ln(x)\cos(1+(\ln(x))^2)\ dx$$

Evaluating the derivative, one gets

$$\begin{align}\frac12I'(t)&=\Im\frac{-\sqrt{\pi i}}4\frac d{dt}e^{i+\frac{(2it+1)^2}{4i}}\operatorname{erf}\left(\frac{2iu+2it+1}2\sqrt i\right)\\&=\Im\frac{-\sqrt{\pi i}}4e^{i+\frac{(2it+1)^2}{4i}}\left[(2it+1)\operatorname{erf}\left(\frac{2iu+2it+1}2\sqrt i\right)+\frac{4i}{\sqrt\pi}e^{-\left(\frac{2iu+2it+1}2\sqrt i\right)^2}\right]\end{align}$$

Finally,

$$\int\ln(x)\cos(1+(\ln(x))^2)\ dx=\Im\frac{-\sqrt{\pi i}}4\left[e^{i+\frac1{4i}}\left[\operatorname{erf}\left(\frac{2iu+1}2\sqrt i\right)+\frac{4i}{\sqrt\pi}e^{-\left(\frac{2iu+1}2\sqrt i\right)^2}\right]\right]$$

Where $u=\ln(x)$.

$\endgroup$
1
1
$\begingroup$

First, substitute via $u=1+\ln^2(x)$ and use the complex exponential form of cosine to get \begin{align*} \int \ln(x) \cos(1+\ln^2(x)) \,dx &= \int \sqrt{u-1}\, \cos(u)\, \frac{\exp(\sqrt{u-1})}{2\sqrt{u-1}} \,du \\ &= \frac{1}{2} \int \cos(u)\,\exp(\sqrt{u-1}) \,du\\ &= \frac{1}{2} \int \frac{1}{2}[\exp(iu)+\exp(-iu)] \,\exp(\sqrt{u-1}) \,du \\ &= \frac{1}{4} \left[ {\int \exp(iu) \,\exp(\sqrt{u-1}) \,du} + \int \exp(-iu) \,\exp(\sqrt{u-1}) \,du \right]\\ &= \frac{1}{4} \left[ I_1 + I_2 \right] \end{align*} Let's deal with $I_1$ first. \begin{align*} I_1 &= {\int \exp(iu) \,\exp(\sqrt{u-1}) \,du}\\ &= \underbrace{-\exp(\sqrt{u-1}) i \exp(iu) }_{\gamma_1} - \int -i\exp(iu)\frac{\exp(\sqrt{u-1})}{2\sqrt{u-1}} \,du\\ &= -\gamma_1 + ie^i\int \exp(a^2i+a) \,da\\ &= -\gamma_1 + ie^i\int \exp\left( i\left[a-\frac{i}{2}\right]^2 +\frac{i}{4} \right) \,da\\ &= -\gamma_1 + i\exp\left(\frac{5i}{4}\right)\int \exp\left( \left[a\sqrt{i} - \frac{i^{3/2}}{2} \right]^2 \right) \,da\\ &= -\gamma_1 + \sqrt{i}\exp\left(\frac{5i}{4}\right)\int \exp\left( z^2 \right) \,da\\ &= -\gamma_1 + \frac{\sqrt{i\pi}}{2}\exp\left(\frac{5i}{4}\right)\,\text{erfi}(z) \end{align*} where the first step uses integration by parts, then the substitution $a=\sqrt{u-1}$ is used, followed by the substitution $z=a\sqrt{i} - i^{3/2}/2$. Recall that $\text{erfi}(z)=-i\,\text{erf}(iz)$.

Now for $I_2$, using a similar strategy. \begin{align*} I_2 &= {\int \exp(-iu) \,\exp(\sqrt{u-1}) \,du}\\ &= \underbrace{\exp(\sqrt{u-1}) i \exp(-iu)}_{\gamma_2} - \int i\exp(-iu)\frac{\exp(\sqrt{u-1})}{2\sqrt{u-1}} \,du\\ &= \gamma_2 - i\int \exp(-ia^2-i+a) \,da\\ &= \gamma_2 - ie^{-i}\int \exp\left( -i\left[a + \frac{i}{2}\right]^2 -\frac{i}{4} \right) \,da\\ &= \gamma_2 - i \exp\left( \frac{-5i}{4} \right) \int \exp\left( -\left[ a\sqrt{i} + \frac{i^{3/2}}{2} \right]^2 \right) \,da\\ &= \gamma_2 - \sqrt{i} \exp\left( \frac{-5i}{4} \right) \int \exp\left( -\zeta^2 \right) \,da\\ &= \gamma_2 - \frac{\sqrt{i\pi}}{2} \exp\left( \frac{-5i}{4} \right) \, \text{erf}(\zeta)\\ \end{align*} using the same subsitution with $a$ and with $\zeta = a\sqrt{i} + i^{3/2}/2$.

Ok, now let's simplify the terms without the error functions: \begin{align*} -\gamma_1 + \gamma_2 &= -\exp(\sqrt{u-1}) i \exp(iu) + \exp(\sqrt{u-1}) i \exp(-iu) \\ &= -\underbrace{\exp(\sqrt{u-1})}_{x}i[\underbrace{e^{iu} - e^{-iu}}_{2i\sin(u)}] \\ &= 2x\sin(1+\ln^2(x)) \\ \end{align*} where we used the complex exponential form of sine.

Next we need to be able to undo the substitutions: \begin{align*} z &= \sqrt{i} a - \frac{i^{3/2}}{2}\\ &= \sqrt{i} \sqrt{u-1} - \frac{i^{3/2}}{2}\\ &= \sqrt{i} \ln(x) - \frac{i^{3/2}}{2}\\ &= \frac{1}{2} \sqrt{i}\left[ 2\ln(x) - i \right]\\ \zeta &= \sqrt{i} a + \frac{i^{3/2}}{2}\\ &= \sqrt{i} \sqrt{u-1} + \frac{i^{3/2}}{2}\\ &= \sqrt{i} \ln(x) + \frac{i^{3/2}}{2}\\ &= \frac{1}{2} \sqrt{i}\left[ 2\ln(x) + i \right] \end{align*}

Now we can put it all together: \begin{align*} \int & \ln(x) \,\cos(1+\ln^2(x)) \,dx \\ &= \frac{1}{4} \left[ I_1 + I_2 \right]\\ &= \frac{1}{4} \left[ -\gamma_1 + \frac{\sqrt{i\pi}}{2}\exp\left(\frac{5i}{4}\right)\,\text{erfi}(z) + \gamma_2 - \frac{\sqrt{i\pi}}{2} \exp\left( \frac{-5i}{4} \right) \text{erf}(\zeta) \right]\\ &= \frac{1}{4} \left( -\gamma_1 + \gamma_2 + \frac{\sqrt{i\pi}}{2} \exp\left(\frac{-5i}{4}\right) \left[ \exp\left( \frac{5i}{2} \right) \text{erfi}(z) - \text{erf}(\zeta)\right] \right)\\ &= \frac{1}{4} \left( 2x\sin(1+\ln^2(x)) + \frac{\sqrt{i\pi}}{2} \exp\left(\frac{-5i}{4}\right) \left[ \exp\left( \frac{5i}{2} \right) \text{erfi}(z) - \text{erf}(\zeta)\right] \right)\\ &= \frac{1}{8} \left( 4x\sin(1+\ln^2(x)) + {\sqrt{i\pi}} e^{\frac{-5i}{4}} \left[ e^{\frac{5i}{2}} \text{erfi}\left(\frac{\sqrt{i}\left[ 2\ln(x) - i \right]}{2} \right) - \text{erf}\left(\frac{\sqrt{i}\left[ 2\ln(x) + i \right]}{2} \right)\right] \right) \end{align*}


A quick check in Mathematica gives:

f[x_] := Log[x] Cos[1 + (Log[x])^2]
FullSimplify[Integrate[f[x], x]]

1/8 ((-1)^(1/4) E^(-((5 I)/4))
  Sqrt[\[Pi]] (-Erf[1/2 (-1)^(1/4) (I + 2 Log[x])] + 
  E^((5 I)/2) Erfi[1/2 (-1)^(1/4) (-I + 2 Log[x])]) + 
  4 x Sin[1 + Log[x]^2])

Which maybe should have been the whole answer...


See also this question, which solves a similar problem.

$\endgroup$
2
  • $\begingroup$ You seem to have solved the wrong problem, as it appears you solved $\int\ln(x)\cos(1+\color{red}2(\ln(x))^2)\ dx$. $\endgroup$ Feb 26 '17 at 14:08
  • $\begingroup$ @SimplyBeautifulArt I believe those were just typos (I've fixed now); thanks for pointing that out! $\endgroup$ Feb 26 '17 at 15:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.